An ATF6-tPA pathway in hepatocytes contributes to systemic fibrinolysis and is repressed by DACH1 - Pestell, Richard George (2019)
Tissue-type plasminogen activator (tPA) is a major mediator of fibrinolysis and, thereby, prevents excessive coagulation without compromising hemostasis. Studies on tPA regulation have focused on its acute local release by vascular cells in response to injury or other stimuli. However, very little is known about sources, regulation, and fibrinolytic function of noninjury-induced systemic plasma tPA. We explore the role and regulation of hepatocyte-derived tPA as a source of basal plasma tPA activity and as a contributor to fibrinolysis after vascular injury. We show that hepatocyte tPA is downregulated by a pathway in which the corepressor DACH1 represses ATF6, which is an inducer of the tPA gene Plat. Hepatocyte-DACH1–knockout mice show increases in liver Plat, circulating tPA, fibrinolytic activity, bleeding time, and time to thrombosis, which are reversed by silencing hepatocyte Plat. Conversely, hepatocyte-ATF6–knockout mice show decreases in these parameters. The inverse correlation between DACH1 and ATF6/PLAT is conserved in human liver. These findings reveal a regulated pathway in hepatocytes that contributes to basal circulating levels of tPA and to fibrinolysis after vascular injury.